Tourism Development Strategy in Kendari City Based on Local Wisdom in Supporting National and Regional Tourism Policies - Idrus, Sitti Hairani; Agus Said, La Ode; Yanti Sari, Siti Kadri; Rijal, Muh.; Syam, Nabila (Ilomata International Journal of Social Science, 2025)
Kendari City has great tourism potential, both in terms of natural beauty and the richness of local wisdom. However, tourism development in Kendari City still faces various challenges, such as lack of local community involvement, promotion that has not been maximized, and inadequate infrastructure. This study aims to analyze tourism development strategies based on local wisdom to support national and regional tourism policies. The results of the study show that the development of tourism based on local wisdom can provide added value for tourism in Kendari City, both in terms of economy and cultural preservation. The recommendations submitted include increasing community involvement in the management of tourist destinations, promotion through digital media, and the development of sustainability-based infrastructure. With the implementation of this strategy, Kendari City tourism is expected to develop optimally and sustainably.